Theories for inflationary era in the early universe - She, Yuhui (Nanyang Technological University, 2024)
In this project, we focus on the single-field slow-roll inflation, with the ultimate goal of exploring the potential relationship between the Higgs potential covered by quantum field theory and the inflaton potential covered by inflationary cosmology. This thesis is divided into three parts. In the Cosmology Background Section, we study the classical background dynamics of inflationary cosmology in the Friedmann-Robertson-Walker spacetime, including the well-known Big Bang puzzles, the conditions for inflation, the diverse inflation models, etc. In the Higgs Field Section, we delve into the Higgs field topic that we aim to explore in greater detail. We discuss the Higgs mechanism and how the spontaneous symmetry breaking process generates mass for gauge bosons. In the Extended Higgs Sector, we go beyond the Standard Model into higher-dimensional Higgs fields and link the Higgs potential with the slow-roll inflaton potential through the vacuum expectation value.